BRIDGING THE GAP BETWEENNEEDS ANALYSIS ANDCOURSE EVALUATION INSIGHTS - Rubina Khan; Tazin Aziz Chaudhury (University of Kuningan, 2013)
Abstract: The â€œAdvancing English Skillsâ€, textbook was compiled and introduced about a decade ago, at the Faculty of Humanities, Dhaka University, Bangladesh, to teach the foundation English courses, to freshmen students from thirteen departments, including English.Â Today the course is still being taught at some departments. The department of English scrapped the foundation course, but the textbook is still being used for another compulsory course. This paper presents the ï¬ndings of a study conducted to determine the English language needs of students (60) and teachers (30) at the Humanities Faculty of Dhaka University. Additionally a two prong evaluation of the course and materials from the viewpoints of both students and teachers of the Humanities faculty was carried out, in order to shed light on the nature, effectiveness, and objectives of the course. Strengths and shortcomings of the present course, and areas of mismatch between the studentsâ€™ needs and the course, were identiï¬ed. Suggestions have been made, to improve the English language courses based on these ï¬ndings, and implications for pedagogy have been highlighted. Keywords: needs analysis, course evaluation, perceptions, ability, mismatch